HIP (HPA-screening in pregnancy) study: protocol of a nationwide, prospective and observational study to assess incidence and natural history of fetal/neonatal alloimmune thrombocytopenia and identifying pregnancies at risk - Winkelhorst, Dian (BMJ Open, 2020)
INTRODUCTION: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) may lead to severe fetal or neonatal bleeding and/or perinatal death. Maternal alloantibodies, targeted against fetal human platelet antigens (HPAs), can result thrombocytopenia and bleeding complications. In pregnancies with known immunisation, fetal bleeding can be prevented by weekly maternal intravenous immunoglobulin infusions. Without population-based screening, immunisation is only detected after birth of an affected infant. Affected cases that might have been prevented, when timely identified through population-based screening. Implementation is hampered by the lack of knowledge on incidence, natural history and identification of pregnancies at high risk of bleeding. We designed a study aimed to obtain this missing knowledge. METHODS AND ANALYSIS: The HIP (HPA-screening in pregnancy) study is a nationwide, prospective and observational cohort study aimed to assess incidence and natural history of FNAIT as well as identifying pregnancies at high risk for developing bleeding complications. For logistic reasons, we invite rhesus D-negative or rhesus c-negative pregnant women, who take part in the Dutch population-based prenatal screening programme for erythrocyte immunisation, to participate in our study. Serological HPA-1a typing is performed and a luminex-based multiplex assay will be performed for the detection of anti-HPA-1a antibodies. Results will not be communicated to patients or caregivers. Clinical data of HPA-1a negative women and an HPA-1a positive control group will be collected after birth. Samples of HPA-1a immunised pregnancies with and without signs of bleeding will be compared with identify parameters for identification of pregnancies at high risk for bleeding complications. ETHICS AND DISSEMINATION: Ethical approval for this study has been obtained from the Medical Ethical Committee Leiden-The Hague-Delft (P16.002). Study enrolment began in March 2017. All pregnant women have to give informed consent for testing according to the protocol. Results of the study will be disseminated through congresses and publication in relevant peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT04067375.